2009
DOI: 10.1002/ijc.24868
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem/progenitor cells are highly enriched in CD133+CD44+ population in hepatocellular carcinoma

Abstract: Both our previous study and other reports have suggested that CD133, originally classified as a hematopoietic stem cell marker, could be used for enrichment of cancer stem cells (CSCs) in human hepatocellular carcinoma (HCC). It was also noted that not all of CD133 1 cells were representative of CSCs. Further identification and characterization of CSCs or tumor-initiating cells in HCC are necessary to better understand hepatocarcinogenesis. In present study, we demonstrated that CSC phenotype could be precisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
322
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(343 citation statements)
references
References 54 publications
18
322
3
Order By: Relevance
“…This cell population is further characterized by the co-expression of CD133 and CD44 (7). Importantly, a significant difference in ABCG2 expression was observed between CD133 Ăž /CD44 Ăž cells and a corresponding double negative subpopulation.…”
Section: Introductionmentioning
confidence: 91%
“…This cell population is further characterized by the co-expression of CD133 and CD44 (7). Importantly, a significant difference in ABCG2 expression was observed between CD133 Ăž /CD44 Ăž cells and a corresponding double negative subpopulation.…”
Section: Introductionmentioning
confidence: 91%
“…Within the CD133 + population, cells with the expression profile CD133 + CD44 + have been described as more tumorigenic and metastatic than CD133 + CD44 − cells (29,30). Other studies have suggested the mucin-like cell surface glycoprotein CD24 (31) and the glycosylphosphatidylinositol-anchored glycoprotein CD90 or Thy-1 (32) as liver CSC markers.…”
Section: Liver Progenitor Cells and Cancer Stem Cellsmentioning
confidence: 99%
“…Several miRNAs such as miR-328, miR-373 and miR-520c have been reported to regulate CD44 and promote cancer cell motility or invasion [64][65][66]. In addition, CD44 has recently been recognized as a cell surface marker of CSC and mesenchymal stem cells (MSC) [67][68][69][70][71][72]. Therefore, these CD44-regulating miRNAs may function in CSC and MSC.…”
Section: Mirnas Modulate Cancer Angiogenesismentioning
confidence: 99%
“…The oncogenic miR-17-92 cluster is not only induced by transcriptional factors c-Myc, E2F [36][37][38], but also by Hedgehog signaling [115,116], which suggests that this cluster may play a role in promoting self renewal of cancer stem cells. miR-328, miR-373, and miR520c have been reported to regulate CSC surface marker CD44 and may promote CSC proliferation and motility [67][68][69][70][71][72].…”
Section: Mirnas Modulate Metastatic Colonizationmentioning
confidence: 99%